The Role of Islamic Religious Education in Enhancing Primary School Accreditation: A Library Research Analysis of Preparation and Implementation Stages - Pebriana, Risma; Julaiha , Siti (Al-Qalam Institue, 2025)
This study aims to examine the concepts, implementation, and challenges of innovation and continuous improvement in Islamic Education (IE) in the digital era through a literature review. A systematic search of national and international journal databases was conducted, followed by thematic analysis to synthesize key findings. The results indicate that: (1) Islamic Education contributes to the development of learning documents aligned with the National Education Standards, such as lesson plans, teaching modules, and competency-based assessments; (2) interactive, values-based Islamic Education fosters a culture of mutual respect and strengthens the school environment; (3) the use of digital technology in evaluation and documentation supports accreditation instruments; and (4) the success of accreditation improvement is influenced by leadership, teacher competency in Islamic Education, and a continuous academic supervision system. This study concludes that optimizing Islamic Education through enhancing process standards, student character, and innovative teaching media is crucial in improving primary school accreditation outcomes. Recommendations are made for educational institutions and policymakers to develop integrated Islamic Education strategies within quality assurance systems.